Pengaruh Informasi Keuangan dan Non Keuangan Terhadap Initial Return pada Perusahaan yang Melakukan IPO di Bursa Efek Indonesia pada Tahun 2019-2021 - Khatimah, Khusnul; Khalid, Ansyarif (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to determine the effect of financial and non financial information as measured by Earning per Share (EPS), Return On Assets (ROA), Debt to Equity Ratio (DER), Leverage Level and Company Age on Intial return in companies that conduct an IPO and be listed on the Indonesia Stock Exchange.The type of research used in this research is quantitative research. The sample in this study is a manufacturing company that conducts an initial public offering (IPO) and is listed on the Indonesia Stock Exchange in 2019-2021 using the purposive sampling method. Purposive sampling is a sampling technique with certain criteria which results in a total sample of 23 companies. The type of data used in this research is quantitative data in the form of annual financial reports. Data sources used in data collection include secondary data. The data analysis classical assumptions. The purpose showed that partially based on the T-Test Earning Per Share (EPS) had a positive and significant effect on Initial Return. Return On Asset (ROA), Debt To Equity Ratio (DER), Leverage Level and Company Age have no effect on Intial Return.